Teenage Reproductive Health: Pregnancy, Contraception, Unsafe Abortion, Fertility - Jon Øyvind Odland (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Maternal mortality is still globally high and reducing it is a top priority. Teenage pregnancies have more complications and are also unwanted in many cases. This contributes to the high maternal mortality with both obstetric complications and burden of unsafe abortion. Additionally, many teenagers live in areas with heavy pollution that affects the mother and the unborn child. Global public health is a very important issue that aims to prevent disease, prolong life, and promote physical, mental and social well-being. Teenagers are the future, and maternal death is a disaster that should be prevented. Hence, research should aim to improve teenage reproductive health and influence policy makers. There are a variety of topics in this issue, with some conclusions and ways forward as described in different papers in this book.